Discovery and Designation of Type Specimens of Chrysomelidae (Coleoptera) From Argentina Described by E. von Harold in 1875 - David G. Furth; Ingolf S. Askevold; Catherine N. Duckett (Psyche: A Journal of Entomology)
Type specimens of 14 species of Chrysomelidae from Cordova, Argentina. collected by W. M. Davis and described by E. von Harold in 1875, were discovered in the collections of the Museum of Comparative Zoology (Harvard University). A few specimens from some other museums such as the Museum für Naturkunde der Humboldt-Universität (Berlin), The Natural History Museum (London), Institut Royal des Sciences Naturelles de Belgique (Brussels), Museo Nacional de Hungaria (Budapest) are also apparently from the original series. Lectotypes and paralectotypes are designated for all species.